The formation of volatile fatty acids in the rumen contents of cows in vivo and in vitro - Lampila, Martti; Poijärvi, Ilmari (Agricultural and Food Science, 1959)
On a diet containing fodder sugar beets the proportion of butyric acid in the mixture of the volatile fatty acids of the rumen contents was found to be unusually high. When the rumen contents were incubated at different pH-levels in vitro, it was found that the proportion of butyric acid in the volatile fatty acid mixture produced increases when the pH decreases. Using polyethylene glycol as a reference substance, the transfer of fluid through the reticulo-omasal orifice was studied. The transfer of volatile fatty acids into the omasum is calculated on the basis of the fluid flow and on the acid concentrations of the fluid in the lower anterior part of the contents.